Optimasi Krim Tabir Surya Ekstrak Daun Beluntas (Pluchea Indica (L). Less ) - Sandya Ayu Marasita, Tarisa; Suproborini, Arum; Kusumawati, Desi (Universitas PGRI Madiun, 2026)
With the return to nature movement, the medicine and cosmetics industry is herbal-based. Seeing that beluntas leaves have potential as antioxidants and have flavonoid compounds as antioxidant parameters. The aim of this research was to see the optimal sunscreen formula of 96% ethanol extract of beluntas leaves based on different formula concentrations. The results of the research obtained beluntas leaves which were in accordance with the determination results. The best formula optimization is in formula 3 with the addition of Tween 80 and Span 80. The characteristic test results meet the characteristics in accordance with the requirements which have a pH that is in the range of 3.5-8.0. In the spreadability test of 5.5 and the viscosity test in accordance with the requirements, it ranges from 2000 cp -50,000 cp.